2019
DOI: 10.1186/s41687-019-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting patient-important outcomes through group brainstorming: when is saturation reached?

Abstract: Purpose Group brainstorming is a technique for the elicitation of patient input that has many potential uses, however no data demonstrate concept saturation. In this study we explore concept saturation in group brainstorming performed in a single session as compared to two or three sessions. Methods Fifty-two predominately African American adults patients with moderately to poorly controlled Diabetes Mellitus participated in three separate group brainstorming sessions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…We found that AL has a greater impact on students' cognitive proficiency, which is consistent with the results of previous investigators (Haukoos and Penick, 1983;Martin et al, 2007;Cordray et al, 2009;Jensen et al, 2015). Our study tried to respond to the concern of the medical faculty communities to redesign our courses into dynamic, student-centered learning domains that engage our students in researchbased learning, problem solving and enhanced personnel development (Wood, 2003;Ma and Lu, 2019;LaNoue et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…We found that AL has a greater impact on students' cognitive proficiency, which is consistent with the results of previous investigators (Haukoos and Penick, 1983;Martin et al, 2007;Cordray et al, 2009;Jensen et al, 2015). Our study tried to respond to the concern of the medical faculty communities to redesign our courses into dynamic, student-centered learning domains that engage our students in researchbased learning, problem solving and enhanced personnel development (Wood, 2003;Ma and Lu, 2019;LaNoue et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…The sample size was relatively small, and 13 out of 16 patients identified as female. However, concept saturation, 24 , 35 defined as the point at which no new important concepts are gleaned from the qualitative interviews, was reached, indicating the sample size was adequate for this purpose. Nevertheless, evaluation of the NFBrSI‐24's performance in a larger sample will be informative.…”
Section: Discussionmentioning
confidence: 99%
“…The entire study was conducted in close collaboration with our Patient Advocate and Key Stakeholders Advisory Board (PAKSAB). The study received institutional IRB approval [9, 10].…”
Section: Methodsmentioning
confidence: 99%